Struktur Mitos dalam Me’eraji: Kajian Strukturalisme Claude Lévi-Strauss - Dama, Yunus; Mohamad, Hawaria; Djua, Nurain; Yunus, Nur Maya; Mustapa, Vidya P.; Saiful, Sumarni; Hulantu, Nurain (Jurusan Pendidikan Bahasa & Sastra Indonesia, Universitas Negeri Gorontalo, 2025)
This article discusses the Me’eraji tradition that developed among the Gorontalo community by utilizing Claude Lévi-Strauss’ structuralism approach, which focuses mainly on reading binary oppositions within the framework of mythological narratives. This tradition was chosen because it contains not only spiritual and religious aspects, but also describes the collective perspective of the community through symbolism and stories that are passed down from generation to generation. The main objective of this study is to analyze the structure of the Me’eraji myth, identify the narrative elements (mythemes) that are its components, and interpret the meaning and social role of the tradition in Gorontalo culture. By using qualitative methods and myth narrative analysis, this study attempts to contribute to the understanding of the richness of oral traditions in Indonesia within the framework of cultural structuralism. Keywords: Me’eraji, structuralism, Claude Lévi-Strauss, myth narrative, Gorontalo culture